DOP53 Clinical, endoscopic, histological and biomarker activity following treatment with the gut-selective, pan-JAK inhibitor TD-1473 in moderately to severely active ulcerative colitis. (25th January 2019) - Sandborn, W; Nguyen, D; Ferslew, B; Hao, L-Y; Kanno, T; Tomsho, L; Boyle, D; Graham, R; Abhyankar, B; Panes, J
Abstract: Background: TD-1473 is an orally administered and gut-selective pan-Janus kinase (JAK) inhibitor that, at doses up to 270 mg, results in low systemic exposure and high concentration in gut tissue which is anticipated to result in local pan-JAK inhibition. The aim was to assess the clinical and molecular effects of TD-1473 in subjects with moderately to severely active UC after 4 weeks of treatment. Methods: In this double-blind, placebo-controlled, multi-centre Phase 1b study, 40 subjects were enrolled and administered placebo ( n = 9), 20 mg ( n = 10), 80 mg ( n = 10), or 270 mg ( n = 11) TD-1473 once daily for 28 days after meeting eligibility criteria (including Mayo rectal bleeding subscore of ≥1, stool frequency subscore of ≥1, and centrally read endoscopic subscore of ≥ 2). Clinical and histological outcomes were assessed by central reading for modified Mayo endoscopic scores and Robarts' Histologic Index (RHI), respectively. Colonic tissue biomarker protein levels and transcriptomics were measured by ELISA and RNAseq, respectively, at baseline and at Day 28. Results: There were trends for higher rates of clinical response, endoscopic healing, and improvement by ≥1 point in rectal bleeding and endoscopy subscores with TD-1473 relative to placebo. Conclusion: Signals for clinical, endoscopic, histological, and biomarker activity were observed in subjects with moderately to severely active UC treated with TD-1473.